Optimal Management with Potential Regime Shifts - Stephen Polasky; Aart de Zeeuw; Florian Wagener (Tinbergen Institute, 2010)
We analyze how the threat of a potential future regime shift affects optimal management. We use a simple general growth model to analyze four cases that involve combinations of stock collapse versus changes in system dynamics, and exogenous versus endogenous probabilities of regime shift. Prior work has focused on stock collapse with endogenous probabilities and reaches ambiguous conclusions about the effect of potential regime shift on optimal management. We show that all other cases yield unambiguous results. In particular, with endogenous probability of regime shift that affects system dynamics the potential for regime shift causes optimal management to become precautionary.
Keywords: E61; O40; Q20; C61; 330; optimal management; growth; renewable resources; regime shift; Systemtransformation; Erneuerbare Ressourcen; Wirtschaftliche Anpassung; Ressourcenökonomik